Complete mitochondrial genome of Sinilabeo decorus tungting (Cypriniformes, Cyprinidae). (3rd March 2016) - Li, Chuanwu; Liang, Zhiqiang; Li, Hong; Yuan, Xiping
Abstract: The complete mitochondrial genome of Sinilabeo decorus tungting was determined in this study. The gene composition, arrangement and transcriptional orientation in S. decorus tungting mitogenome were identical to most vertebrates. Two start codon patterns (ATG and GTG) and three stop codon patterns (TAG, TAA and T) were found in protein-coding genes. Only the tRNA-Ser2 could not fold into a typical clover-leaf secondary structure for lacking the dihydrouridine arm. Sequences alignment results suggest that the complete mitogenome of S. decorus tungting is an efficient tool to check species identification by comparing different gene sequences.